PENENTUAN KERAGAMAN KARAKTER TANAMAN MANGGIS MELALUI IDENTIFIKASI MORFOLOGI DAN ANATOMI DAUN TANAMAN MANGGIS (Gracinia mangostana L.) DI KABUPATEN MOROWALI UTARA - Enny Adelina, Sakka Samudin, Ni Putu Lilis H.W, (AGROTEKBIS, 2016)
This study aims to investigate the characteristics of mangosteen based on the morphology and anatomy of leaves in the north Morowali District. Morphologhy observations were made in the Olomukunde, Taliwan and Tomata villages. The observations anatomy conducted in the plant pest and disease science laboratory and also in science and seed technology science laboratory, Faculty of agriculture Tadulako University from December-February 2016. The results showed that the character morphology and anatomy observed based on the cluster analyse and presented in the form of a that can be. The results of cluster showed that from 3 villages was yield one-4 acsesi the Morowali Districts, objectives this research was to indicated as first step to be found the random plent. The result of the research indicated the apart 0.7 found 4 groups plant there are on the KA6, KA10, TA10 dan PA2 sample. The lowest stomata index on the leaf from three villages of KA7 sample. The lowest stomata index on the PA9. The highest index of stomata on the PA4 sample and the lowest index of stomata that is TA6 Sample.